A Computational Thinking Course for Pre-Service Teachers - Oliveira, Eduardo C. (2022)
Computational Thinking (CT) is a set of thinking processes used by computer scientists to formulate problems and describe solutions. In recent years, CT has been largely explored by the Computing Education community. Due to its potential to contribute to problem solving and analytical thinking, CT could also be a relevant subject in K-12 education. For such, there is a need to qualify educators in CT. In this paper, we describe our experience in a large-scale course on Computational Thinking for pre-service teachers. Our goal is to qualify pre-service teachers in CT, both in the comprehension of its definition and how it can be incorporated in classroom. Our experience indicates that the participants had a positive awareness of CT concepts, as well as an adequate understanding of the pedagogical approaches to teach the subject. They also developed positive attitudes towards the field of Computer Science.